NATURAL RESOURCES AND ANTHROPOGENIC FACTORS OF TOURISM DEVELOPMENT IN CLUJ - Daniela PLEȘOIANU; Cristina GURALIUC (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The paper presents the tourism sector in the county of Cluj, combining physical and geographical, historical and economic elements favored over time by the emergence of tourism activities in the area. This paper presents an analysis of several components of the tourism sector as well as tourism potential of the county, adjacent infrastructure and sector-specific types and forms of tourism practiced in Cluj by the existing natural potential, movement and tourism demand. The major objectives of this work are: establishment of the potential attractiveness of the county by inventorying and assessing its natural and anthropogenic aspects; determining the extent to which infrastructure present here is valued and able to contribute to the economic development of the county and determining how tourist traffic has evolved over time. The data were provided by Cluj County Council, Cluj County Development Strategy 2007 - 2013, and National Institute of Statistics, Cluj. The data were processed and converted into tables, graphs and then analyzed. The presence in various proportions of the attractive natural resources and the different accessibility of the road network and the position in the territory of Cluj-Napoca - a nodal landmark, the dispersion of tourist flows in Cluj County and the entire region of North -West constitute the favorable conditions for practicing a wide variety of different types and forms of tourism. (with whom they could develop new forms, provided accommodation is in charge of planning and modernization, diversification and functional readjustment ) and allow drawing a tourism profile.